Improving Wheat Yield Prediction Using Secondary Traits and High-Density Phenotyping Under Heat-Stressed Environments - Rahman, Mohammad Mokhlesur; Crain, Jared; Haghighattalab, Atena; Singh, Ravi P.; Poland, Jesse (Frontiers in Plant Science, 2021)
A primary selection target for wheat (Triticum aestivum) improvement is grain yield. However, selection for yield is limited by the extent of field trials, fluctuating environments, and the time needed to obtain multi-year assessments. Secondary traits such as spectral reflectance and canopy temperature (CT), which can be rapidly measured many times throughout the growing season, are frequently correlated to grain yield and could be used for indirect selection in large populations particurally in earlier generations in the breeding cycle prior to replicated yield testing. While proximal sensing data collection is increasingly implemented with high-throughput platforms that provide powerful and affordable information, efficiently using this data is challenging. The objective of this study was to monitor wheat growth and predict grain yield in wheat using high-density proximal sensing measurements under extreme terminal heat stress that is common in Bangladesh. Over five field seasons, we analyzed normalized difference vegetation index and CT measurements collected in elite breeding lines from the International Maize and Wheat Improvement Center at the Regional Agricultural Research Station, Jamalpur, Bangladesh. We explored several variable reduction and regularization techniques followed by using the combined secondary traits to predict grain yield. Prediction accuracy was calculated via a cross-fold validation approach as the correlation between observed and predicted grain yield using univariate and multivariate models. We found that multivariate models resulted in higher prediction accuracies for grain yield than the univariate models. Stepwise regression performed equal to, or better than, other models in predicting grain yield. When incorporating all secondary traits into the models, we obtained high prediction accuracies of 0.58 to 0.68 across the five growing seasons. Our results show that optimized phenotypic prediction models can leverage secondary traits to deliver highly accurate predictions of wheat grain yield, allowing breeding programs to make more robust and rapid selections.